2005
DOI: 10.1002/bit.20664
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hydrogen‐dependent denitrification under varying pH and temperature conditions

Abstract: It is important to determine the effect of changing environmental conditions on the microbial kinetics for design and modeling of biological treatment processes. In this research, the kinetics of nitrate and nitrite reduction by autotrophic hydrogen-dependent denitrifying bacteria and the possible role of acetogens were studied in two sequencing batch reactors (SBR) under varying pH and temperature conditions. A zero order kinetic model was proposed for nitrate and nitrite reduction and kinetic coefficients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
3
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 18 publications
2
68
3
6
Order By: Relevance
“…Our K value of 1.3 mg BrO À 3 /L is the first reported K value for bromate reduction. For hydrogen oxidizing, autotrophic denitrifying bacteria, previous studies showed a q max ¼ 0.38-0.74 (Rezania et al, 2005) and K ¼ 0.18-0.16 mg N/L (Kurt et al 1987). For hydrogen oxidizing, autotrophic perchlorate-reducing bacteria, the parameters were q max ¼ 3.1 mg ClO (Nerenberg et al, 2006).…”
Section: Bromate Reduction Kineticsmentioning
confidence: 93%
“…Our K value of 1.3 mg BrO À 3 /L is the first reported K value for bromate reduction. For hydrogen oxidizing, autotrophic denitrifying bacteria, previous studies showed a q max ¼ 0.38-0.74 (Rezania et al, 2005) and K ¼ 0.18-0.16 mg N/L (Kurt et al 1987). For hydrogen oxidizing, autotrophic perchlorate-reducing bacteria, the parameters were q max ¼ 3.1 mg ClO (Nerenberg et al, 2006).…”
Section: Bromate Reduction Kineticsmentioning
confidence: 93%
“…Carrier materials used in these systems have an extremely high specific surface area which allows high biomass concentrations and, thus, the treatment of high nitrate loadings. Several studies report higher denitrification rates in biofilm systems such as fixed-bed or fluidized-bed reactors compared to suspended growth reactors [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies on hydrogenotrophic denitrification reported in the literature, only few of them use biological kinetic data to facilitate the design and operation of biological nitrogen removal plants [10,[13][14][15] and even less study the kinetics of the biofilm process in a hydrogenotrophic denitrifying reactor [16]. However, modelling of denitrifying biofilm reactors has been carried out by several authors in heterotrophic [17,18] and sulphur autotrophic [19,20] denitrification.…”
Section: Introductionmentioning
confidence: 99%